Use of Residential Blood Pressure Monitoring as a Tool in Pharmaceutical Care – Baseline Assessment of the MINOR Clinical Trial - Maciel Moreira, Pablo; Miranda de Paula, Sabrina; Canguçu Aguiar, Erlan; Ribeiro de Castro, Priscila; Coelho de Almeida, Kleiton; Dourado, July Anne; Flores Melo, Milena; Moura Santos, Pablo; Galvão Oliveira, Márcio (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: Hypertension is a chronic condition that requires constant monitoring and adjustment of drug therapy. Home Blood Pressure Monitoring (HBPM) has proven to be an effective tool in this process, allowing for a more accurate assessment of blood pressure outside of the clinical setting. Objective: To evaluate the contributions of the use of HBPM devices in the monitoring and evaluation of antihypertensive therapy in patients served by a public clinical pharmacy service. Methods: A longitudinal study with secondary analysis was conducted, using the IBM SPSS Statistics software, of the data aggregated to the MINOR Clinical Trial database, registered on ClinicalTrials under number NCT04861727 and approved by the Research Ethics Committee of the Federal University of Bahia (Opinion No. 4.595.144). Results: In the initial assessment with HBPM, 22.98% of participants (n=74) presented hypotension, only 15.84% (n=51) presented controlled hypertension, and 61.18% of individuals (n=166) were identified with uncontrolled hypertension. After pharmaceutical interventions, the proportion of patients with hypotension decreased to 20.81% (n=67), the proportion of controlled hypertension increased to 36.34% (n=117), while the proportion of uncontrolled hy-pertension decreased to 42.86% (n=138). Conclusion: The use of HBPM demonstrated positive contributions to the optimization of antihypertensive drug therapy and proved to be a useful tool in the clinical practice of the pharmacist, contributing to adequate blood pressure control, identification of hypotensive users and candidates for deprescribing.